"It is easy for women to ask!": Gender and digital finance in Kenya. Issue 2 (10th May 2018) - Kusimba, Sibel
Abstract : This article examines the role of gender in the use of digital finance in Kenya, including the well‐known case of mobile money but also the emerging use of smartphone apps, payment tills, digital credit services, and digital fund‐raising computer programs. Development professionals have explicitly feminist goals in bringing digital finance to women in the Global South. In several recent reports, they outline the belief that gender norms are a barrier to women's use of finance. They hope digital finance will bring women agency and control over money and consequently shift restrictive gender norms. This article offers a critique of these assumptions based on ethnographic conversations, a diary exercise, and network self‐portraiture conducted in Kenya in 2016 among both rural farmers and urbanites. Adopting a distributed agency perspective, the ethnographic study demonstrates that Kenyan women and men use digital finance not to seek individual control of their money but to produce themselves as connected and trustworthy members of financial groups and collectivities. Gender norms may not hinder women from finance but rather enhance and deepen women's and men's financial relationships and bring women success in amassing funds.